Strategies in the design and use of synthetic "internal glycan" vaccines - Lakshminarayanan, A; Vijayakrishnan, B; Bayley, H; Davis, B (Elsevier, 2017)
The relative structural conservation of "internal glycans" in the cell walls of pathogens suggests that they might as target epitopes less prone to variation and hence with greater potential universality as vaccine targets. Examples of such glycans include the inner core sugars of lipopolysaccharides in Gram-negative bacteria. However, due to the buried nature of such internal epitopes, this approach has been rarely adopted. Here we briefly review and compare strategic approaches and outline practical methods associated with evaluating one synergistic strategy that combines (i) blocking of the display of "external glycans" with (ii) vaccination targeted at "internal glycans."